A Comparative Study Between Islamic and Public High Schools on Multicultural Self-Efficacy - Yosef Yosef (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
Having adequate multicultural self-efficacy enables students to get along, learn, and collaborate confidently and harmoniously with culturally diverse peers in any school setting. However, there is only a small number of research on this matter for the dual types of Indonesian secondary schools. The objective of this study was to compare Islamic and public high school students on multicultural self-efficacy. A 36-item Multicultural Self-Efficacy Scale for High School (MSES-HS) measured the multicultural self-efficacy of 246 Islamic and Public high school students in an online survey. It consisted of cultural insight, communication, cultural value, cultural awareness, and flexibility subscales. Results indicated that most of the students’ multicultural self-efficacy in both schools fell from a moderate to the highest level, except for small numbers at a low and a lower level. The current study found that the multicultural self-efficacy levels of Islamic and public high school students were not different significantly. In terms of differences by grade levels and gender, the study indicated similar results. The study highlighted findings to guidance and counseling services and suggestions to expand the investigation.